A Note on Linear Multiplier Fractional \(q\)-Differintegral Operator With Varying Arguments - Ahmed, Rmsen Abdulbari Ali; Ravikumar, N. (Communications in Mathematics and Applications, 2025)
We introduce new subclasses of analytic functions with varying arguments by making use of linear multiplier fractional \(q\)-differintegral operator. For functions belonging to these classes, we obtain coefficient estimates, distortion theorems, extreme points, \(q\)-Bernardi integral operator, and many more properties.
Keywords: Analytic function; Univalent function; Fractional \(q\)-differintegral operator; \(q\)-Bernardi operator